(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2018)
Background: Contrast-induced nephropathy (CIN) is the third leading cause of hospital-acquired acute renal failure. Objective: The purpose of the present study was to compare the incidence and associated risk factors of contrast induced nephropathy in diabetes and non-diabetic patients. Methodology: This was cross-sectional study performed in the Department of Nephrology at National Institute of Kidney Diseases and Urology, Sher-E-Bangla Nagar, Dhaka and Department of Cardiology, Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh from January 2016 to July 2016. Contrast induced nephropathy (CIN) is defined as increase in serum creatinine of ≥25% from baseline value and/ or an absolute increase of ≥0.5 mg/dl in serum creatinine from baseline. Patients were divided in to two groups Group A (Patients with Diabetes mellitus) and Group B (Patients without Diabetes mellitus). To identify independent characteristics associated with CIN, multivariable logistic regression analysis was used through SPSS version 23. Results of this model were presented as Odds Ratio (OR). P value was calculated to see the significance of various risk factors in diabetes and non-diabetes patients. Results: The difference in baseline creatinine serum creatinine was found statistically significant (P<0.001). In group A 57 patients (50.9%) had eGFR <60ml/min/1.73m2, 55 patients (49.1%) had eGFR ≥60ml/min. The difference in estimated GFR was found statistically significant (P<0.001). Left ventricular ejection fraction <40% was present in 6 (5.4%), 7 (5.1%) in group A and B respectively, ≥40% in 106 (94.6%), 131 (94.9%) in group A and B respectively. CIN developed in 21 (18.80%) patients in group A and 2 (1.4%) patients in group B (CIN was defined by increased in serum creatinine ≥25% of baseline or ≥44μmol/L). All belonged to group A, 16 (19%) of the diabetic patients out of 86 developed CIN. Diabetic patients who had eGFR <60ml/min (n=30), 13 (43.3%) developed CIN. Among all patients (n=250), 23 developed CIN. Overall incidence was 9.2%. Conclusion: CIN was significant developed in diabetes group than non diabetes. Left ventricular ejection fraction and total volume of contrast media used was significantly higher in diabetes group than non-diabetes group B patients. Journal of National Institute of Neurosciences Bangladesh, 2017;3(1): 29-36